2012
DOI: 10.1007/s10562-012-0842-0
|View full text |Cite
|
Sign up to set email alerts
|

Methanation of Carbon Dioxide Over Mesoporous Nickel–M–Alumina (M = Fe, Zr, Ni, Y, and Mg) Xerogel Catalysts: Effect of Second Metal

Abstract: Mesoporous nickel (35 wt%)-M (5 wt%)-alumina xerogel (denoted as 35Ni5MAX) catalysts with different second metal (M = Fe, Zr, Ni, Y, and Mg) were prepared by a single-step sol-gel method for use in the methane production from carbon dioxide and hydrogen. In the carbon dioxide methanation reaction, yield for CH 4 decreased in the order of 35Ni5FeAXThis indicated that the catalytic performance was greatly influenced by the identity of second metal in the carbon dioxide methanation reaction. Experimental results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 35 publications
7
45
0
Order By: Relevance
“…Nickel, iron, and ruthenium contents in the 35Ni5FexRuAX catalysts determined by ICP-AES analyses were in good agreement with the designed values. All the 35Ni5FexRuAX catalysts exhibited high surface area, large pore volume, and large average pore diameter, in good agreement with the previous work [14]. The above results indicate that mesoporous nickel-iron-ruthenium-alumina xerogel catalysts were successfully prepared by a single-step sol-gel method as attempted in this work.…”
Section: Physicochemical Properties Of 35ni5fexruax Catalystssupporting
confidence: 90%
See 2 more Smart Citations
“…Nickel, iron, and ruthenium contents in the 35Ni5FexRuAX catalysts determined by ICP-AES analyses were in good agreement with the designed values. All the 35Ni5FexRuAX catalysts exhibited high surface area, large pore volume, and large average pore diameter, in good agreement with the previous work [14]. The above results indicate that mesoporous nickel-iron-ruthenium-alumina xerogel catalysts were successfully prepared by a single-step sol-gel method as attempted in this work.…”
Section: Physicochemical Properties Of 35ni5fexruax Catalystssupporting
confidence: 90%
“…It has been reported that adsorption ability of a metal catalyst for carbon dioxide can be modulated by adding an appropriate second metal [14,30]. This implies that addition of ruthenium into nickel-iron-alumina xerogel catalyst might affect the catalytic Table 2 Catalytic performance of 35Ni5FexRuAX (x = 0, 0.2, 0.4, 0.6, 0.8, and 1.0) catalysts for methane production from carbon dioxide and hydrogen obtained at 220 8C after a 10 hcatalytic reaction.…”
Section: Co 2 -Tpd Experiments Of 35ni5fexruax Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…At high space‐velocities, catalysts such as Ni/Al 2 O 3 reach the maximum conversion only above 400–450 °C. Modification of the support and incorporation of a second metal promote the CO 2 conversion performance, but long‐term stability is still often an issue. Recently, other types of materials with enhanced catalytic performance have also been reported .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, addition of a second metal, such as Sm, Ce, and Fe, has been performed to enhance the catalytic activity and stability of Ni-based catalysts for CO methanation reaction; the second metal can improve dispersion of the active metal and adjust the interaction between Ni and the support [19e23]. Hwang et al [20,21] prepared NieMealumina xerogel catalysts doped with a different second metal (M ¼ Fe, Ni, Co, Ce, and La) through solegel method; they found that the NiFeAX catalyst exhibited excellent catalytic performance for CO or CO 2 methanation at low reaction temperatures. Yi Cheng et al [22] found that bimetallic NieFe alloy was more active than traditional Ni-based catalysts for CO methanation.…”
Section: Introductionmentioning
confidence: 99%